Motor learning and control concepts and applications - Magill, Richard A.; Anderson, David 1965 December 21- (McGraw-Hill Education, 2021)
Motor Learning and Control: Concepts and Applications, 12e, is an introduction to the study of motor learning and control for students who aspire to become practitioners in exercise science, physical education, and other movement-oriented professions. Each chapter presents motor learning and control as a set of principles and guidelines based on research evidence. The authors' clear writing style and practical applications will help students build a solid foundation and prepare them for further exploration on their own.